Efeito antibacteriano do ácido anacárdico em culturas planctônicas e biofilmes de Streptococcus mutans - Sousa, Denise Lins de (2014)
Anacardic acid is an extract from processing of cashew nut shell liquid (CNSL) and it has been recognized to have several biological activities. This study is divided into three chapters, whose aims were: chapter 1) to investigate the antibacterial activity of an anacardic acids emulsion, from CNSL, and a synthetic emulsion of anacardic acid against pianktonic cuitures of S. nuitaris as well as to evaluate its cytotoxic effect in vitro; chapter 2) to evaluate the effect of different concentrations of an anacardic acids emulsion against Sfreptococcns imitans mature biofilm: and chapter 3) to evaluate the effect of a single and daily treatment of an anacardic acids emulsion against Streptococcus niutans biofilm. The antibacterial activity of the emulsions was determined using the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), and the cytotoxicity was evaluated using CellTiter-Blue® cell viability (chapter 1). The biofilms were grown on hydroxyapatite discs and immersed in tryptone yeast-extract broth containing 1% (w/v) sucrose for 5 days. The biofilms were exposed to anacardic acids emulsion for 1 min on the last day of experiment to evaluate its effect on mature biofilm; bacterial viability and dry weight were analyzed (chapter 2). Different concentrations of anacardic acids emulsion were applied on the last day of the experiment and twice daily until the fifth day to evaluate the effects of different treatments of anacardic acids emulsion on 5. mutans biofilms; bacterial viability, dry weight and polysaccharides were analyzed (chapter 3). The MBC and MIC of the anacardic acids emulsion (from CNSL) on planktonic culture were 0.48 pg/ml; the MIC of the synthetic emulsion of anacardic acid was 4.38 pg/ml, but the MBC could not be determined (> 3,200 ug/ml) (chapter 1). Significant decreases in the viability of mature biofilms were observed after anacardic acids emulsion treatment, but they did not change the amount of dry weight (chapter 2). The daily treatment with different concentrations of anacardic acids emulsion decreased the bacterial viability and modified the polysaccharides leveis on biofilm (chapter 3). We concluded that anacardic acids emulsion is a promising antibacterial agent, and it can decrease S. mutans viability in planktonic cultures and in biofilms.